The application of seaweed-based food products for ketogenic diet: opportunities and prospects - Phang, Siew Moi; Lee, Yu Zhao; Tham, Chau Ling; Ho, Yu Cheng; Lee, Ming Tatt (Elsevier, 2025)
The ketogenic diet has been the subject of research as a dietary intervention for various health conditions. It is known to induce a metabolic state called ketosis via limiting carbohydrate intake and significantly increasing fat consumption in diet. The body then transitions from glucose-dependent metabolism to utilizing ketone bodies as fuel source. However, the long-term adherence is one of the main challenges in ketogenic diet for sustained implementation and therapeutic efficacy. Seaweed-based food products, characterized by relatively low carbohydrate content, high mineral density, rich bioactive substances and functional polysaccharides, may provide support in metabolic health. This review article evaluates seaweed-derived products that are suitable for inclusion in ketogenic diet. From the analysis of the available scientific literature, the inclusion of seaweed in ketogenic dietary patterns for healthy individuals is of great potential. The integration of seaweed-based food products into ketogenic diets has the potential to enhance nutritional adequacy while maintaining the strict macronutrient ratios. The nutritional content of seaweed-based food products demonstrates low net carbohydrate content, moderate protein levels, and valuable fatty acid profiles, thus compatible with ketogenic diet principles. Furthermore, the high dietary fiber content of seaweeds may reduce the possible impact of total carbohydrate content on the ketogenic carbohydrate limitations. Interestingly, various bioactive substances that showed antioxidant, anti-inflammatory, neuroprotective effects, etc., are also abundantly found in seaweed extracts, which further enhance their implementation in ketogenic diet. In conclusion, the review summarized the beneficial characteristics of seaweed-based food products that support the prospects of their inclusion in ketogenic diets.